Transceiver Design for Intelligent Reflecting Surface-Assisted Simultaneous Wireless Information and Power Transfer Systems - Liong, Hui Jing (Curtin University, 2024)
Intelligent reflecting surface (IRS) has emerged as a potential technology for meeting the performance requirements of 6G systems. Transceiver design is essential for IRS-assisted systems to unleash the full potential of IRS for optimal performance. This thesis focuses on optimizing the transceiver design for the IRS-assisted multi-user MIMO SWIPT system, considering both perfect and imperfect channel state information. The proposed designs outperform the benchmarks in terms of sum-rate while fulfilling the Quality of Service requirements.